2015
DOI: 10.1002/jobm.201400865
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel cold‐adapted phytase from Rhodotorula mucilaginosa strain JMUY14 isolated from Antarctic

Abstract: A yeast producing a cold-adapted phytase was isolated from Antarctic deep-sea sediment and identified as a Rhodotorula mucilaginosa strain JMUY14 of basidiomycetous yeasts. It was cultured in fermentation optimized by a response surface methodology based on the Box-Behnken design. The maximum activity of phytase reached 205.447 U ml(-1), which was close to the predicted value of 201.948 U ml(-1) and approximately 3.4 times higher than its initial activity. The extracellular phytase was purified by 15.2-fold to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 24 publications
2
17
1
Order By: Relevance
“…The maximum phytase activity (26.51 U/mg) was achieved at 144 h of fermentation (Figure 2(d)). This period for enzyme production was minor than that mentioned for production of phytase by Rhodotorula mucilaginosa JMUY [32]. On the other hand, it was higher than that observed for enzyme production by Rhizopus microsporus var.…”
Section: Kinetic Of Phytase Production By Muscodor Spcontrasting
confidence: 54%
“…The maximum phytase activity (26.51 U/mg) was achieved at 144 h of fermentation (Figure 2(d)). This period for enzyme production was minor than that mentioned for production of phytase by Rhodotorula mucilaginosa JMUY [32]. On the other hand, it was higher than that observed for enzyme production by Rhizopus microsporus var.…”
Section: Kinetic Of Phytase Production By Muscodor Spcontrasting
confidence: 54%
“…Cold-adapted phytases might have considerable advantages in direct inclusion in feed for monogastric animals and use in aquaculture [79]. Pavlova et al [78] reported that Papiliotrema laurentii AL27 (formerly Cryptococcus laurentii) showed highest intracellular phytase activity at an optimal temperature of 40.0 C. In another study, Yu et al [79] reported the production of extracellular phytase by Rhodotorula mucilaginosa JMUY14, which showed resistance to both pepsin and trypsin degradation after purification.…”
Section: Other Hydrolytic Enzymesmentioning
confidence: 99%
“…The techniques used were diverse and yielded purification factors from 1.70-to 1568.00-fold and yield ranging from 0.65 to 86.20%. Enzymes secreted into the medium by Antarctic fungi are first concentrated by techniques, such as ultrafiltration [68,74,80,81,98,130], ammonium sulfate precipitation [63,64], ammonium sulfate and dialysis [79,85], or acetone precipitation [107]. After concentrating, the protein, purification can be carried out by a single or multiple steps of chromatography.…”
Section: Purification Of Cold-adapted Enzymes From Antarctic Fungimentioning
confidence: 99%
“…The application of phytase as the feed supplement has encouraged researchers to develop economical strategies to produce the enzyme in a cost-effective manner. Although a number of fungi, yeast, and bacteria are known to produce phytases [3,4,28,29], none of them produce adequate enough to produce it on a large scale. The cloning and over expression of the enzymes is an approach that permits enzyme manufacture in a cost-effective manner.…”
Section: Resultsmentioning
confidence: 99%